Conservation in the 21st century - thinking big, the public good, and private lands - Hayes, John, speaker; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2014)
Conservation and stewardship of our natural resources have been fundamental to the missions of a number of our public agencies in the United States since their inception. However, as important as public lands have been for conservation in the United States, most of the nation's land is in private ownership. The amount, distribution, and characteristics of private lands, combined with the spatial scales at which ecological systems operate, create a special and critical conservation role for private lands. While many of the strategies for conservation on public lands are also effective on private lands, private lands present special opportunities for conservation, as well as special challenges. As is true in many regions, conservation on private lands has played a critical role in sustaining wildlife, biodiversity, and ecosystems in Northern Colorado. Examples of innovative conservation partnerships and efforts focused on conservation of private lands in the region are presented. Lessons learned from these case studies and the shifting dynamics facing our natural systems suggest a number of lessons and future directions in conservation, education, and research.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
Presented during Welcome Remarks & Plenary Session I.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses